Development and evaluation of novel, personalisable electronic counselling aids for patients starting Direct Oral Anticoagulants (DOACs) - Whitney, Jennifer Marie (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2022)
Comprehensive education for patients taking DOACs is essential to ensure treatment is safe and efficacious. The prescribing of DOACs has increased since becoming available on the European market in 2008, as evidence shows reductions in major bleeding incidences compared to VKAs and their noninferiority with respect to overall efficacy in treatment. Knowledge questionnaires have been developed as a counselling aid to ensure essential knowledge points have been retained adequately by OAC patients. Electronic education techniques also have the potential to overcome current challenges faced by healthcare professionals in patient counselling, such as time-shortages. Novel techniques must be developed and validated in a standardised manner, with personalisation of content for each individual patients. Chapter 1 provides a background into anticoagulant therapy and the conditions they treat. Chapter 2 is a comprehensive literature review of existing questionnaires that assess patients knowledge and understanding of OACs. Searches were made of the PubMed (MEDLINE), EMBASE and Cochrane library databases, for studies outlining the development and validation of knowledge questionnaires for patients taking OACs. The searches included studies published in English with no date restrictions. Manual searches of relevant papers reference lists were also conducted. A total of 6 studies were included which outlined the development and validation of knowledge tools. A further 4 papers were found that utilised the original knowledge tools in a different population of patients. Comparisons were made between each tool and the quality of the validation methods used. Further research is required to investigate the efficacy of knowledge questionnaires and their relation to patient outcomes. Chapter 3 details a preliminary analysis of the English translation of the Jessa Atrial Fibrillation Knowledge Questionnaire (JAKQ). Healthcare professionals with experience and expertise in the area of DOACs, AF and VTE were recruited to evaluate the content of the questionnaire. A small sample size of patients attending TUH s AF clinic were also recruited to complete the questionnaire which revealed areas in the tool which could be improved. A larger scale study is required to complete the validation of the JAKQ amongst patients in Ireland. Chapter 4 explores a review of the current literature associated with electronic patient education methods for those taking OACs. Electronic searches were made using PubMed (MEDLINE), EMBASE and google scholar to identify relevant RCTs and quasi-RCTs. Studies published in English that met the criteria were included. A total of 5 studies were included for qualitative analysis. Cochrane s Tool for assessing risk of bias in randomised trials was utilised. Although findings were generally positive, limitations such as small sample sizes meant that recommendations for practice could not be made based on this review. Further research using larger sample sizes is need to increase the power of the results. Chapter 5 assesses the quality of counselling resources for patients taking DOACs. Resources were identified: (a) through targeted searches of the manufacturers websites and the websites of patient support organisations and government health agencies in relevant countries; (b) through structured internet searches combining terms of interest. The content of resources was evaluated against recommendations from two leading international bodies: the EHRA and the iPACT. The Flesch Reading Ease and Flesch-Kincaid Grade Level scores were determined for resources targeted at patients, to assess their readability. Cosgrove s Readability Checklist was also used to gain insight into the presentation and format. Based on the findings, a counselling aid for pharmacists was creating to standardise the information found. Chapter 6 outlines the development of a personalisable, electronic counselling aid for patients taking DOACs. The process involved content design to establish the primary counselling points, graphic design to create the counselling aid, and presentation of the tool to bring all elements together. The educational tool has the potential to assist in the counselling of patients taking DOACs for AF, DVT and PE. Future work is needed to conduct a high-quality RCT for this counselling aid to understand the impact it could have. Chapter 7 provides a summary of the chapters, overall conclusions and future work that can build upon the research conducted.
APPROVED
Keywords: Oral Anticoagulant Patients, Knowledge Questionnaires, Electronic Counselling, DOACs